2011
DOI: 10.1128/jvi.00870-11
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Dual Antiviral Role of the Major Nuclear Domain 10 Component Sp100 during the Immediate-Early and Late Phases of the Human Cytomegalovirus Replication Cycle

Abstract: In recent studies, the nuclear domain 10 (ND10) components PML and hDaxx were identified as cellular restriction factors that inhibit the initiation of human cytomegalovirus (HCMV) replication. The antiviral function of ND10, however, is antagonized by the IE1 protein, which induces ND10 disruption. Here we show that IE1 not only de-SUMOylates PML immediately upon infection but also directly targets Sp100. IE1 expression alone was sufficient to downregulate endogenous Sp100 independently of the presence of PML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 55 publications
15
71
0
Order By: Relevance
“…In accordance with previous studies, PML was found to be partially deSUMOylated upon infection ( Fig. 1 A) (29,40). While most high-molecular-weight bands of PML disappeared, one presumably modified species of PML seemed to be resistant against IE1 action (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In accordance with previous studies, PML was found to be partially deSUMOylated upon infection ( Fig. 1 A) (29,40). While most high-molecular-weight bands of PML disappeared, one presumably modified species of PML seemed to be resistant against IE1 action (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, this complete loss of PML as a consequence of MHV-68 infection presumably also accounted for the simultaneously observed disappearance of the low-mobility isoforms of Sp100 (Fig. 1B, lane 2), comparable to the situation in herpes simplex virus type 1-infected cells (7) or after depletion of the defining ND10 factor in HFFs by short hairpin RNA-mediated knockdown of PML (12,36). Intriguingly, PML protein levels remained completely unaltered following infection with HVS (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Since sumoylation of PML is essential for the integrity of ND10, this leads to a dispersal of the subnuclear structure. Interestingly, we and others could recently show that IE1 can also directly affect Sp100 (20,36). In particular, at late times of the human CMV (HCMV) replicative cycle, a proteasomal degradation of Sp100 was observed; however, degradation was dependent on the additional presence of viral true late gene products (20,36).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations